2019
DOI: 10.1177/1947603519890754
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Assessment of MACI Grafts in Patients with Revision Surgery and Total Joint Arthroplasty

Abstract: Objective To compare the histological and immunohistochemical characteristics of matrix-assisted chondrocyte implantation (MACI) grafts between patients with revision surgery and patients with total joint arthroplasty. Methods Biopsies of MACI grafts from patients with revision and total joint arthroplasty. The graft tissue characteristics and subchondral bone were examined by qualitative histology, ICRS (International Cartilage Repair Society) II scoring and semiquantitative immunohistochemistry using antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…Limited subchondral cyst formation was observed in some participants in zones beneath the area of chondral regeneration or at the interface of regenerative and native cartilage. These cysts were stable between 12 and 36+ months and have been observed in other cartilage graft techniques including Matrix-induced Autologous Chondrocyte Implantation and microfracture [67].…”
Section: Discussionsupporting
confidence: 64%
“…Limited subchondral cyst formation was observed in some participants in zones beneath the area of chondral regeneration or at the interface of regenerative and native cartilage. These cysts were stable between 12 and 36+ months and have been observed in other cartilage graft techniques including Matrix-induced Autologous Chondrocyte Implantation and microfracture [67].…”
Section: Discussionsupporting
confidence: 64%
“…Recently, Beck et al, with the histological evaluation on MACI implants, observed that all failed implants were characterized by fibrous involution independently from patients' clinical conditions [28]. Those results may explain the poor correlation we observed between clinical and radiological scores at long-term FU.…”
Section: Discussionmentioning
confidence: 65%
“…McCarthy et al found subchondral bone cysts under the lesion area in 14.7% patients treated with either first-or second-generation ACI at 1 year postoperatively, 25 considerably lower than the data from previous cohorts treated with microfracture (38.5% at 1 year postoperatively) from Cole et al 58 Correspondingly, a recent clinical investigation from biopsies of patients undergoing total knee arthroplasty as a salvage procedure for failed second-generation ACI with an average graft survival period of 26.8 months identified subchondral bone cyst formation within 20% of patients. 61 In a 9-18 years follow-up study, subchondral cysts were reported in 38.8% knee defects treated with firstgeneration ACI. 59 Merkeley et al identified the presence of severe BME (grade IV) as a predictive factor for graft failure (n = 8) among patients (n = 38) receiving a salvage second-generation knee ACI for failed prior marrow stimulation.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 98%
“…dral bone changes in the context of cartilage repair exposed variable patterns, including the formation of subchondral bone cysts (Figure 1), intralesional osteophytes, generalized upward migration of the subchondral bone plate, and the presence of residual marrow stimulation hole(s), together with peri-hole or generalized bone resorption (Table 1). 51,52 With a view of systematically exploring each of these morphologic changes in both preclinical 46,47,[53][54][55][56][57] and clinical 25, [58][59][60][61][62][63][64][65][66] settings, an adjustable algorithm has been recently proposed to radiographically analyze them ( Figure 2). 52 In this algorithm, the projected tidemark and cement line serve as topographical landmarks.…”
Section: A Systematic Analytic Algorithm For Cyst Formation In the Sumentioning
confidence: 99%
See 1 more Smart Citation